Arran Stibbe (Ecolinguística: Revista brasileira de ecologia e linguagem (ECO-REBEL), 2021)
Arran Stibbe is Professor of Ecological Linguistics at the University of Gloucestershire. He has an academic background in both linguistics and human ecology and combines the two in his research and teaching. He is the founder of the International Ecolinguistics Association, and author of Animals Erased: Discourse, Ecology and Reconnection with Nature.